The European Football Championship
XII, 180 p.
Keywords: The UEFA European football championship was the first European mega-event to take place in post-socialist Europe. Taking this as a departure point, this volume focuses on football as a realm of constructing and negotiating identities using rich ethnographic fieldwork and in-depth media analysis.